Identifying key sectors and key policies of a pro-poor growth strategy - Christian Henning; Johannes Hedtrich (Kiel Institute for the World Economy (IfW), Poverty Reduction, Equity and Growth Network (PEGNet), 2017)
There is a broad agreement that sustainable and pro-poor growth is the only successful strategy to reduce poverty. However, putting Pro-Poor-Growth (PPG) into operation is a complex task. A prominent debate concerns the relative importance of agriculture versus non-agricultural sectors in promoting PPG. Empirical studies usually find that agricultural growth has larger economy-wide multiplier effects and stronger linkages to poverty reduction in most African countries. For example, Diao et al. (2012) conclude from their Computable General Equilibrium (CGE) simulations undertaken for Kenya and Rwanda that 1 percent GDP growth driven by agriculture leads to three or four times more poverty reduction than 1 percent GDP growth driven by non-agriculture. Such findings are intuitive, considering the stronger multiplier effects of agriculture (and especially staple food crops) on household incomes, consumption and overall economic growth. However, alternative concepts identifying key sectors exist that partly lead to different results (Henning et. al. 2016). [...]
Keywords: 330